International agreement on the regulation of conflict-of-law relations - TYSHCHENKO Юлія (Ius Modernum, 2023)
An international agreement is a legal institution of international public law, but it is necessary to study the peculiarities of its operation and application as a source of international private law. In the field of legal regulation of private legal relations complicated by a foreign element, there is a tendency to harmonize and unify the legislation of different countries, especially at the level of the European Union and similar integration associations. The international agreement is the main instrument in these unification processes. The purpose of the article is to clarify the specifics of the operation and application of an international agreement as a form of international private law, as well as to establish the consequences of withdrawing from multilateral international agreements for relations, which are the subject of this sphere. General scientific and special methods, such as: system-functional, deduction method, analysis, comparative-legal method, were chosen as the methodological basis of the research. The legal norms of international acts and domestic legislation, scientific works and judicial practice became the information base. It has been established that the definition of an international agreement is presented in international legal acts, which are based on the norms of domestic legislation, as well as scientific doctrine. The issue of the place of international agreements, which do not require the ratification of the Verkhovna Rada, in the hierarchy of normative legal acts according to the criterion of legal force, as well as the problem of the effect of such international agreements in case of reference to them by the norms of domestic laws, has been considered. The consequences of the suspension of action and the withdrawal of Ukraine from a number of international agreements that regulated private legal relations, complicated by a foreign element, are analyzed and ways to eliminate the legal gaps associated with such withdrawal are proposed. The correlation of legal norms presented in bilateral and multilateral international agreements on the same issues has been established. A proposal for the adoption of a legislative act has been proposed, which would determine the legal force of normative legal acts.